Lived experiences of Educators in relation to CPTD within the Johannesburg West District High Schools - Costa, King; Thusi, Nisi (My University, 2020)
Continuing Professional Teacher Development (CPTD) is empowerment and enhancement of professionalism and competence of Educators within the education system, whether public or private sector. The Department of Basic Education implemented a standardized CPTD program throughout the schooling system, which is monitored and managed by a statutory body known as SACE (South African Council of Educators). This study sought to describe lived experiences of educators in relation to implementation of CPTD in Johannesburg West District. The study was designed within the interpretivist paradigm, employing phenomenology as a strategy of inquiry. 10 educators were selected purposively for interviews, which were recorded with permission of participants. The recording was critical for demonstration of member checking and audit trail required for rigor determination in qualitative research. Through thematic data analysis, the study generated three themes in pursuit of answering the research question, which were (1) Mentorship Vacuum, (2) Dis-interest and inertia and (3) Leadership Support. Whereas the first two themes report the negative experiences educators have had with CPTD, the last them reflected that participants had some form of leadership support.
Keywords: CPTD; Educators; Leadership Support; Mentorship